1984
DOI: 10.1104/pp.76.3.833
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Proteinase Inhibitor-Inducing Activities and Phytoalexin Elicitor Activities of a Pure Fungal Endopolygalacturonase, Pectic Fragments, and Chitosans

Abstract: Rhizopus stolonifer endopolyglacturonase, an elicitor of casbene synthetase activity in castor bean seedlings, was found to be a potent elicitor of the phytoalexin pisatin in pea pods and of proteinase Inhibitor I in tomato leaves. The enzyme was an active elicitor or inducer only in its active native state; heat-denatured enzyme was inactive in all three systems. The activities of (a) the tomato pectic polysaccharide proteinase inhibitor-inducing factor, (b) a partially acid hydrolyzed proteinase inhibitor-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(35 citation statements)
references
References 17 publications
1
33
0
1
Order By: Relevance
“…Numerous genetic and physiological studies show a clear link between jasmonate signalling and the induction of local and systemic defenses in plants. In addition to elevated jasmonate levels, exogenous methyl-jasmonate application also activates many of the same systemic responses [107,[115][116][117] and genes [115,118,119] as chitin-based treatments in plants, which also indicates a link between chitin treatment and jasmonate activation of defenses. Elevations in the level of the stress hormone ABA has also been found following chitin-based treatments [120] and both are known to reduce stomatal aperture [121].…”
Section: Detection Of Chitin In Plantsmentioning
confidence: 99%
“…Numerous genetic and physiological studies show a clear link between jasmonate signalling and the induction of local and systemic defenses in plants. In addition to elevated jasmonate levels, exogenous methyl-jasmonate application also activates many of the same systemic responses [107,[115][116][117] and genes [115,118,119] as chitin-based treatments in plants, which also indicates a link between chitin treatment and jasmonate activation of defenses. Elevations in the level of the stress hormone ABA has also been found following chitin-based treatments [120] and both are known to reduce stomatal aperture [121].…”
Section: Detection Of Chitin In Plantsmentioning
confidence: 99%
“…However, only the stigma w a s wounded 8 to 10 c m from the ovary. With regard to wound reactions, it also has been shown that membrane properties do change in leaves that are distant from those wounded, resulting in the formation of more fragile protoplasts (Walker-Simmons et al, 1984). Other authors (Gaspar et al, 1985) suggested that stress-induced membrane depolarization leads to generation of free radicals and peroxides, which cause breakdown of membrane lipids.…”
Section: I Sc U Sslonmentioning
confidence: 99%
“…This detected elicitation could, however, be due partly to chitin oligomers that may have been released from the insoluble chitin by enzymes secreted by the suspension-cultured cells (Felix et al, 1993). Chitin oligomers have been shown to act as potent elicitors of protease inhibitor and chitinase activities, of polyphenolic compounds, and of severa1 phytoalexins (Kohle et al, 1984;Walker-Simmons et al, 1984;Roby et al, 1987).…”
Section: Environmental Stressmentioning
confidence: 99%